Planetary Cities: Fluid Rock Foundations of Civilization. (March 2022) - Clark, Nigel
Whereas recent framings of planetary urbanization stress the planet-scaled impacts of contemporary urban processes, we might also conceive of cities as being constitutively 'planetary' from their very outset. This article looks at two ways in which the earliest urban centres or 'civilizations' on the floodplains of the Fertile Crescent harnessed the deep, geological forces of the Earth. The first is the tapping and channelling of sedimentary processes, central to what Wittfogel referred to as hydraulic civilizations (1963). The second is the use of high-heat technologies to smelt and forge metals, which can be construed as a capture of igneous processes. What both sets of practices have in common is that they involve skilled intervention in fluid-solid phase transitions between solid rock and flowing particulate matter. Viewing cities as constitutively geological or planetary in this way can help us reimagine the challenges posed to urban spaces by looming transformations in Earth systems.